UNDERSTANDING LANGUAGE TOWARD A COMPREHENSIVE DEFINITION - Xaydarova Nigora; Rakhmatillaeva Gulzirakhon (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Language is more than a tool for communication; it shapes our thoughts, beliefs, and relationships. Through language, we express ideas, share emotions, and form our understanding of the world. It influences how we see ourselves and how we interact with others in society. This article discusses why language matters and how it affects our perceptions, identities, and social connections. By examining examples from literature, media, and everyday life, we explore the powerful role language plays in shaping both individual experiences and social dynamics.